Acute oral toxicity evaluation of andrographolide self-nanoemulsifying drug delivery system (SNEDDS) formulation - Arba Pramundita Ramadani; Yandi Syukri; Elma Hasanah; Afrizal Wahyu Syahyeri (Wolters Kluwer Medknow Publications, 2021)
Context: Andrographolide (AND) is an active compound of well-known medicinal plant Andrographis paniculata. It has been widely published for various activities. AND is difficult to develop into dosage form due to its poor solubility and bioavailability. This problem could be solved by using self-nanoemulsifying drug delivery system (SNEDDS) for its formulation. However, the increase of bioavailability might result in potential toxicity as a large amount of drug is absorbed. Aims: The aim of this study is to evaluate the acute potential toxicity using Organization for Economic Cooperation and Development (OECD) test: 401 methods. Subjects and Methods: The OECD 401 method employs groups of animals treated by a single dose or repeated dose (<24 h) of the drug with three variances of doses. In this study, thirty male Wistar rats were divided into five groups which consisted two groups of control and three groups of AND SNEDDS formulation (500, 700, and 900 mg/kg body weight [BW], respectively). Intensive observation of toxicity symptom was performed during the first 30 minutes followed by periodic observation for 14 days. Posttermination, histopathological examination of the liver and kidney was conducted to confirm the toxicity symptoms. To determine the level of toxicity, the lethal dose 50 (LD50) value was calculated at the end of the study. Results: The result showed that all groups presented similar toxicological symptoms such as salivation, lethargy, and cornea reflex. However, based on histopathological examination, there were abnormalities, but still in an early stage. The toxicological symptom that emerged seems related to the SNEDDS formulation with lipophilic properties. Furthermore, the value of LD50 was 832.6 mg/kg BW (po). Conclusions: The AND SNEDDS formulation was slightly toxic in male Wistar rats po.